2014
DOI: 10.1186/2049-3258-72-25
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with data quality in the routine health information system of Benin

Abstract: BackgroundRoutine health information systems (RHIS) are crucial to the acquisition of data for health sector planning. In developing countries, the insufficient quality of the data produced by these systems limits their usefulness in regards to decision-making. The aim of this study was to identify the factors associated with poor data quality in the RHIS in Benin.MethodsThis cross-sectional descriptive and analytical study included health workers who were responsible for data collection in public and private … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 9 publications
1
66
1
1
Order By: Relevance
“…These systems may be routine health information systems (RHIS) that "provide information at regular intervals of a year or less through mechanisms designed to meet predictable information needs" [24]. In Benin, a data quality assessment including a health worker survey (n=116) noted that the health professionals were inadequately qualified, as few had been trained on RHIS and the training received had not always been fit for purpose [25]. Kenya established their RHIS in 1984; however, 55% (67) of health workers had no knowledge about it [20].…”
Section: Skills and Understanding Of The Routine Health Information Smentioning
confidence: 99%
“…These systems may be routine health information systems (RHIS) that "provide information at regular intervals of a year or less through mechanisms designed to meet predictable information needs" [24]. In Benin, a data quality assessment including a health worker survey (n=116) noted that the health professionals were inadequately qualified, as few had been trained on RHIS and the training received had not always been fit for purpose [25]. Kenya established their RHIS in 1984; however, 55% (67) of health workers had no knowledge about it [20].…”
Section: Skills and Understanding Of The Routine Health Information Smentioning
confidence: 99%
“…Assessment in multiple countries showed that system design issues were related to complexity of systems, multiple forms to enter and use, and system responsiveness to user information needs . The people‐related problems were similar across different studies and included motivation to use data, data use training, and supervisory support …”
Section: Resultsmentioning
confidence: 99%
“…24 The people-related problems were similar across different studies and included motivation to use data, data use training, and supervisory support. 33,37,38 literature. Furthermore, review findings showed that individual training efforts primarily focus on imparting data analysis skills and neglect system design skills, such as requirement gathering, user-centered design, and usability evaluation, even though evidence shows that poor system design accounts for most of the issues that HIS users encounter.…”
Section: System Design Barriersmentioning
confidence: 99%
“…A data collector collects or supplies data for the PHIS. Of the 45 articles, 23 assessed the performance of data collectors 14,[29][30][31]33,35,[38][39][40]44,46,47,49,51,55,57,59,60,62,66,[68][69][70] (see Table 1). Details of facilitators and barriers for data collector are shown in Supplemental Appendix Table 2. A data collector is a stakeholder with whom the data user should build up and nurture a relationship.…”
Section: Data Collectormentioning
confidence: 99%